Calibrating the cosmic-ray energy scale of the Pierre Auger Observatory using radio detection of extensive air showers in AERA - Büsken, Max (Comisión Nacional de Energía Atómica; Argentina. Gerencia de Área Académica. Gerencia Instituto de Tecnología "Jorge Sabato", 2025)
Fil: Büsken, Max. Comisión Nacional de Energía Atómica; Argentina. Instituto de Tecnología "Jorge Sabato"